1993
DOI: 10.1080/00332747.1993.11024621
|View full text |Cite
|
Sign up to set email alerts
|

Children’s Exposure to Community Violence: Following a Path from Concern to Research to Action

Abstract: This paper discusses the antecedents and current progress of an ongoing program of research on the nature, extent, and consequences of children's direct and indirect exposure to violent events and settings. Involvement in such research has sensitized the authors to difficult ethical and methodological challenges that, we believe, merit consideration by mental health scientists and policy markers. Resolution of those challenges has substantive implications for both subsequent research and the application of res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
107
0
4

Year Published

1997
1997
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 160 publications
(115 citation statements)
references
References 11 publications
2
107
0
4
Order By: Relevance
“…Anderson, 1994Anderson, , 1999Durant et al, 1994;Hoffman, 2004). What soon emerged from our discussions with these young offenders was the conclusion that such fatalism emanated from their day to day experiences with and witnessing of violence: These observations on inner-city life echo previous studies of urban violence which have depicted such communities as "war zones," where much of the violence that occurs is public (taking place on the street or in alleys and parks), and where even young children witness aggravated assaults and murders (e.g., Bell and Jenkins, 1993;Garbarino et al, 1992;Hoffman, 2004;Lorion and Saltzman, 1993). For example, based on a large sample of young people drawn from Chicago's inner-city schools, Bell and Jenkins (1993) determined that three out of four had witnessed a robbery or some other type of serious violent crime.…”
Section: Results Of Studysupporting
confidence: 76%
See 3 more Smart Citations
“…Anderson, 1994Anderson, , 1999Durant et al, 1994;Hoffman, 2004). What soon emerged from our discussions with these young offenders was the conclusion that such fatalism emanated from their day to day experiences with and witnessing of violence: These observations on inner-city life echo previous studies of urban violence which have depicted such communities as "war zones," where much of the violence that occurs is public (taking place on the street or in alleys and parks), and where even young children witness aggravated assaults and murders (e.g., Bell and Jenkins, 1993;Garbarino et al, 1992;Hoffman, 2004;Lorion and Saltzman, 1993). For example, based on a large sample of young people drawn from Chicago's inner-city schools, Bell and Jenkins (1993) determined that three out of four had witnessed a robbery or some other type of serious violent crime.…”
Section: Results Of Studysupporting
confidence: 76%
“…These experiences with violence contribute to a pervasive sense of fear and vulnerability in such communities (Lorion and Saltzman, 1993) (Eitle and Turner, 2002;Farrell, 1997; see also Margolin and Gordis, 2000;Scarpa, 2003Scarpa, , 2001). Predictably, our interviewees described their own lives and neighborhoods as plagued by the persistent threat of violence.…”
Section: Results Of Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Some effects of witnessing community violence have been identified as acting out behavior (Eth & Pynoos, 1985), higher levels of stress (Fitzpatrick & Boldizar, 1993;Lorion & Saltzman, 1990;Osofsky et al, 1993), more depression (Freeman, Mokros & Poznanski, 1993; and belligerence (Green et al, 1991). DuRant and his colleagues (DuRant et al, 1994a;DuRant, Pendergrast & Cadenhead, 1994b) have shown that adolescents' exposure to violence and their own victimization are associated with subsequent use of aggressive and violent behaviors.…”
Section: Community Violencementioning
confidence: 99%